Risk of Cerebral Embolism After Interventional Closure of Symptomatic Patent Foramen Ovale or Atrial Septal Defect: A Diffusion-Weighted MRI and Neuron-Specific Enolase-Based Study - (:unkn) unknown (H M P COMMUNICATIONS, 2013)
Objectives. The aim of this single-center prospective study is to investigate the silent and clinically apparent cerebral embolic events after transcatheter closure of atrial septal defect (ASD) and patent foramen ovale (PFO). Background. Although transcatheter closure of ASD and PFO is a widely accepted technique and has been proven to be safe and effective with different kinds of devices, there are few studies in the literature that report the peri-interventional cerebral embolism risk and neurological complications. In this study, we investigated the peri-interventional cerebral embolism incidence with diffusion-weighted magnetic resonance imaging (DW-MRI) and its relation to patients' clinical neurologic examination findings and plasma neuron-specific enolase (NSE) levels. Methods. Sixteen patients with hemodynamically significant ASD and 14 symptomatic PFO patients underwent transcatheter closure procedures with new-generation PFO or ASD occluder devices. All cases were examined with DW-MRI before and after the transcatheter closure procedure. Patients were clinically examined for any signs of neurologic deficit at the time of MRI studies. Blood samples for NSE, a marker of brain tissue damage involved in an ischemic event, were taken before the procedure and at 12 and 24 hours after the procedure. Results. Successful transcatheter closure of PFO or ASD was achieved in all patients. In the DW-MRI exam following the procedure, a new microembolic lesion was found in only 1 of 30 patients (3.3%). None of the patients had positive clinical neurological exam findings. NSE levels after the procedure were found to be not correlated with presence of DW-MRI lesion and intervention times. Conclusion. With the new-generation ASD and PFO occluder devices, the incidence of clinically silent peri-interventional cerebral embolic lesions after transcatheter closure of ASD and PFO is low. Plasma NSE levels offered no additional benefit for monitoring ischemic events after ASD and PFO transcatheter closure procedures.
Keywords: cerebral embolic events; ASD closure; PFO closure; TRANSCATHETER CLOSURE; DEVICE; STROKE; OCCLUDER; PFO